The Function And Meaning Of Umpasa In Toba Batak’s Traditional Wedding Ceremony - Pasaribu, Arsen Nahum (Pascasarjana Universitas HKBP Nommensen, 2023)
This study seeks to reveal the menaing and function of umpasa in Toba Batak’s wedding ceremony.This qualitative research method is based on qualitative content analysis (Marying, 2010). Theresearch data is 40 umpasa of Toba, taken by recording and video-taping 5 wedding ceremoniesheld in Medan. The findings show that the meanings and functions of the umpasa are also closelyrelated to the wedding process of the Toba Batak society and also to Toba Batak’s philosophy.Umpasa is used in Toba Batak’s traditional wedding ceremony to refine and beautify the language.This shows a sense of mutual respect between host and invited guests, especially between hula-hula(the wife giver) and boru (the wife receiver). Of all the umpasa presented at the Toba Bataktraditional wedding ceremony, the meaning and function of umpasa is usually used to show:blessing, respecting, praising, advising, thanking, agreeing, expecting, opening and closing.